Gender dynamics in church leadership: A case study of the Presbyterian Church and Full Gospel Mission in Cameroon - Helen N. Linonge-Fontebo; Magezi E. Baloyi (HTS Teologiese Studies/Theological Studies, 2023)
The biblical creation of woman in which she was taken from man’s rib is one of the passages that are misinterpreted to solidify the subjection and oppression of women with the two Cameroonian Churches, Presbyterian and Full Gospel Mission (FGM). This implies that the complementarity that existed in pre-colonial leadership was eroded as a result. This article will use the qualitative approach to unmask and analyse the practices of gender inequality within the Presbyterian and FGM of Cameroon and the challenges that they are facing with gender equality issues between males and females. The sampling of 22 participants was used to formulate how the findings that will target to unveil the coordination, managerial and financial positions within these two churches are elected or chosen. The stereotypes that are involved in the elections of people who must hold these offices will be explained, discussed and analysed and even exposed in order to seek ways to avoid the manipulations of biblical texts in justifying the exclusion of females from leading church leading positions. This article argues that the misuse of misinterpretation or misrepresentation of scriptures cannot be condoned to justify the marginalisation of women from leadership within the Presbyterian Church in Cameroon (PCC) and the FGM. As much as women are working hard for the church, they should also be allowed to continue growing the church even from the managerial or leadership positions.